Investigating a Coupled Hybrid System of Nonlinear Fractional Differential Equations - Wiyada Kumam; Mian Bahadur Zada; Kamal Shah; Rahmat Ali Khan (Discrete Dynamics in Nature and Society)
We study sufficient conditions for existence of solutions to the coupled systems of higher order hybrid fractional differential equations with three-point boundary conditions. For this motive, we apply the coupled fixed point theorem of Krasnoselskii type to form adequate conditions for existence of solutions to the proposed system. We finish the paper with suitable illustrative example.